Efficacy of Phlogenzyme® in men following transurethral laser enucleation of prostate hyperplasia: results of a randomized trial - S. V. Kotov; S. A. Pulbere; A. G. Yusufov; A. D. Bolotov; R. I. Guspanov; A. P. Semenov; D. A. Bogdanov (Вестник урологии, 2024)
Introduction. The most advanced and eﬀective method of surgical treatment for benign prostatic hyperplasia (BPH) is transurethral laser enucleation of the prostate (tLEP). Recently, there has been a growing interest in exploring new approaches to reduce the risk of complications following tLEP.Objective. To evaluate the eﬃcacy of using Phlogenzym® as part of a comprehensive treatment plan for patients following tLEP to reduce dysuria (urinary discomfort), leukocyturia (white blood cells in urine), and prevent infectious and ﬁbrosis-related complications.Materials & methods. An open-label, randomized trial enrolled 105 patients undergoing tLEP. The patients were randomly assigned to two groups: the study group (n=50) received standard postoperative care in combination with Phlogenzym® for 30 days, while the control group (n=55) received standard care (α1-adrenergic blocker for 28 days) only. uring the follow-up period, which lasted for 1, 3, and 6 months postoperatively, complaints were evaluated using the IPSS-QoL, and IIEF-5 questionnaires, as well as indicators of urinalysis and urine culture, prostate volume measurements, residual urine volume, and uroﬂowmetry data.Results. Among all patients, the median preoperative values for prostate volume, IPSS, QoL score, and median peak urine ﬂow rate were 90 cc, 18 points, 5 points, and 7.9 mL/s, respectively, with no signiﬁcant diﬀerences between the groups. One month after surgery, in the study group, there was a more signiﬁcant decrease in prostate volume (57% vs. 41%), although this diﬀerence was not statistically signiﬁcant (p > 0.05). At the 6-month follow-up, bacteriuria was less common in the study group (42% vs. 67%), and there was a consistent trend toward a reduction in the incidence of ﬁbrous complications, although these diﬀerences were not statistically signiﬁcant either (p > 0.05). No adverse events occurred during the follow-up period.Conclusion. Our experience suggests that the use of Phlogenzym® is safe during the postoperative period following tLEP surgery. The use of this drug leads to a reduction in prostate volume postoperatively and signiﬁcantly reduces the bacteriuria by the six-month follow-up. Additionally, there is a persistent positive trend towards reducing the overall incidence of ﬁbrotic complications in the surgical site. The results achieved and the absence of signiﬁcant side eﬀects characterize Phlogenzym® as having a favorable clinical proﬁle.